Definition:Hilbert Proof System/Instance 2

From ProofWiki
Jump to navigation Jump to search

Definition

This instance of a Hilbert proof system is used in:


Let $\mathcal L$ be the language of propositional logic.


$\mathscr H$ has the following axioms and rules of inference:


Axioms

Let $p, q, r$ be propositional variables.

Then the following WFFs are axioms of $\mathscr H$:

\((A1)\)   $:$   Rule of Idempotence    \(\displaystyle (p \lor p) \implies p \)             
\((A2)\)   $:$   Rule of Addition    \(\displaystyle q \implies (p \lor q) \)             
\((A3)\)   $:$   Rule of Commutation    \(\displaystyle (p \lor q) \implies (q \lor p) \)             
\((A4)\)   $:$   Factor Principle    \(\displaystyle (q \implies r) \implies \left({ (p \lor q) \implies (p \lor r)}\right) \)             


Rules of Inference

$RST \, 1$: Rule of Uniform Substitution

Any WFF $\mathbf A$ may be substituted for any propositional variable $p$ in a $\mathscr H_2$-theorem $\mathbf B$.

The resulting theorem can be denoted $\mathbf B \paren{ \mathbf A \mathbin{//} p }$.

See the Rule of Substitution.


$RST \, 2$: Rule of Substitution by Definition

The following expressions are regarded definitional abbreviations:

\((1)\)   $:$   Conjunction       \(\displaystyle \mathbf A \land \mathbf B \)   \(\displaystyle =_{\text{def} } \)   \(\displaystyle \neg \left({ \neg \mathbf A \lor \neg \mathbf B }\right) \)             
\((2)\)   $:$   Conditional       \(\displaystyle \mathbf A \implies \mathbf B \)   \(\displaystyle =_{\text{def} } \)   \(\displaystyle \neg \mathbf A \lor \mathbf B \)             
\((3)\)   $:$   Biconditional       \(\displaystyle \mathbf A \iff \mathbf B \)   \(\displaystyle =_{\text{def} } \)   \(\displaystyle (\mathbf A \implies \mathbf B) \land (\mathbf B \implies \mathbf A) \)             


$RST \, 3$: Rule of Detachment

If $\mathbf A \implies \mathbf B$ and $\mathbf A$ are theorems of $\mathscr H$, then so is $\mathbf B$.

That is, Modus Ponendo Ponens.


$RST \, 4$: Rule of Adjunction

If $\mathbf A$ and $\mathbf B$ are theorems of $\mathscr H$, then so is $\mathbf A \land \mathbf B$.

That is, the Rule of Conjunction.

(This rule can be proved from the other three and so is only a convenience.)


Also see


Source of Name

This entry was named for David Hilbert.


Sources